Severe cardiac anomalies in sibs with Larsen syndrome. Issue 6 (December 1983) - Strisciuglio, P; Sebastio, G; Andria, G; Maione, S; Raia, V
Abstract : Larsen syndrome is characterised by congenital anterior dislocation of the knees, associated with other joint dislocations, and a characteristic facies. Autosomal recessive and dominant inheritance have been proposed. A brother and a sister with consanguineous parents, suggesting autosomal recessive inheritance, were found to have the typical features of Larsen syndrome. In addition, they had severe cardiac manifestations, never reported before in familial cases of the syndrome. We suggest that the recessive form is probably more severe than the dominant form because of the frequent presence of concomitant cardiac anomalies.